Role of nurses in prevention and nursing of diabetic foot disease (回顾护士在糖尿病足预防和护理中的作用) - GAN Lu (甘露); XIE Wei (谢薇); LIU Qing (刘青); JIANG Yonghong (江永红); YUAN Zheng (袁铮); XIAO Mengyun (肖孟云); MO Mei (莫梅); YUAN Dan (袁丹); CHEN Hongyi (陈红伊); JIANG Qingxia (江青霞); XU Tengfei (徐腾飞); LIU Qiulin (李秋林) (Association of Integrative Nursing, 2022)
Diabetic foot disease is a common and serious complication for diabetes and is characterized with impaired angiogenesis. Nurses are the primary providers of prevention and early diagnosis of diabetes and its complications. This paper summarized the role of clinical nurse specialist in prevention of diabetic foot disease, diabetic foot care and prevention of diabetic foot wounds. In terms of nursing, nurses are responsible for the observation of change in foot soft tissue and skin sensitivity, as well as foot care, dressing and use of the new technologies. In terms of rehabilitation, clinical nurse specialist are responsible for the exercise guidance and health education for patients with foot ulcer and amputated limbs (糖尿病足是糖尿病常见并发症之一, 护士是积极参与预防和早期发现糖尿病及其并发症的卫生保健提供者。本文概述了护士, 尤其是糖尿病专科护士, 在糖尿病足预防和护理中重要作用。在护理方面, 护士负责早期发现皮肤和足部感觉的变化, 开展足部护理、敷料和新技术的应用; 在康复领域, 糖尿病专科护士负责指导和帮助糖尿病足溃疡或截肢患者进行活动。)